BUDAYA PENGOBATAN ETNOMEDISIN DI DESA PORELEA KECAMATAN PIPIKORO SULAWESI TENGAH - Kristiyanto, Jefri; Mamosey, Welly E.; Damis, Mahyudin (Universitas Sam Ratulangi, 2020)
Indonesia is known for its extraordinary natural wealth supported by geographical conditions where plants are variegated easily grown in tropical climates. All kinds of plants in Indonesia can be utilized for the benefit of society such as for treatment. The treatment using ethnomedicine in Indonesia has grown since long ago, supported by geographical conditions where plants are variegated easily to grow in tropical climates. The old kingdoms in Nusantara have developed herbal medicine in the form. Just as the knowledge is empirically known and handed down from generation to generation so that this ancestral inheritance can be guarded. But modern life has unhealthy habits, such as food-ready meals so that many of the less good impacts of food such as preservatives in the ready-to-eat food.People will be more prone to disease, when many are sick of those who run to doctors and doctors using chemical medicines. But on the other hand because the community is still there is a shortage of funds or still there are living areas that are still far away with health centers such as Puskesmas, and society still trust natural materials so that many people still use traditional medicine especially the community that exists in the countryside. Porelea Village is one of the three oldest villages in the highlands of Central Sulawesi's Pipikoro district. Porelea Society knows 2 ways of treatment by using modern medical and traditional medical uses.Keywords: health, treatment, ethnomedicine